The Effect Of Team Games Tournament Model On Arabic Reading Skills In Elementary School - Ulum, Nuzulul; Cristi Crismono, Prima; Munirotun Nahdia, Zannuba (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
This study aims to analyze the effect of the Team Game Tournament (TGT) cooperative learning model on improving Arabic reading skills (maharah qirāʾah) of fourth-grade students at elementary school Nahdlatul Ulama 12 Darun Najah. The research addresses the problem of low Arabic reading ability due to the use of less innovative teaching methods. Research approach a quantitative with a one-group pretest-posttest design was employed. The sample consisted of 24 students selected through purposive sampling. Data were collected through reading skill tests and observations. Data analysis included normality testing, homogeneity testing, paired sample t-test, and effect size calculation using Cohen’s. The results showed that the use of the TGT model significantly improved Arabic reading skills, as evidenced by a p-value of less than 0.05 in statistical tests. Furthermore, TGT created an active, competitive, and collaborative learning environment, enhancing students' motivation and social interaction. In conclusion, the TGT model is effective for improving maharah qirāʾah skills in Arabic language learning at the elementary school level.